Pemanfaatan Teknologi untuk Meningkatkan Numerasi Peserta Didik SMP N 1 Kertanegara - Waluyo, Retno; Kusuma, Rahayu Linda; Zamora, Hanenda Putri (Universitas Pahlawan Tuanku Tambusai, 2024)
Numeracy is very important for junior high school students to learn because it has a significant impact on daily life such as problem solving abilities, critical thinking abilities and the ability to apply mathematical concepts in various situations. The numeracy ability index at junior high school level in Purbalingga Regency is rated